Control strategies for Listeria monocytogenes in ready-to-eat foods and on food contact surfaces - Saini, Jasdeep Kaur (Kansas State University, 2012)
The ubiquitous nature and continued presence in food processing environments makes Listeria monocytogenes a significant threat in ready-to-eat (RTE) food products. This study was performed in two phases; Phase 1 studied lauric arginate (LAE) as an antimicrobial on food contact surfaces and shredded mozzarella cheese, and use of glucose oxidase (GOX), sodium lactate (SL), and acidified calcium sulfate (ACS) as preservatives in mozzarella cheese; Phase 2 evaluated efficacy of Photohydroionization (PHI) technology to control L. monocytogenes on food contact surfaces, sliced American cheese, and ready-to-eat turkey. Stainless steel coupons, mozzarella cheese, American cheese, and turkey were surface inoculated with a three- or five-strain cocktail of L. monocytogenes. Coupons were treated with 100 and 200 ppm solution of lauric arginate for 5 and 15 min. Mozzarella cheese was treated with different combinations of treatments comprising LAE, GOX, SL, ACS, dextrose, and anticaking agents (free flow 1031 and cellulose). Results indicated up to 2.5 log CFU/coupon reductions and it was concluded that LAE was effective in controlling low levels of contamination of L. monocytogenes on food contact surfaces. In mozzarella cheese, results indicated that lauric arginate provided no additional antimicrobial effect (P > 0.05) as compared to GOX + dextrose. The antimicrobial blends with GOX, SL, and ACS were different (P < 0.05) from the controls but showed no differences (P > 0.05) in their effect in controlling bacterial populations. Results from treatment with PHI unit showed significant (P < 0.05) reduction in bacterial populations. L. monocytogenes populations reduced by 4.37 log CFU/coupon on stainless steel surfaces after 15 min of treatment; 2.16 and 2.52 log CFU/sample reduction on American cheese and ready-to-eat turkey, respectively, after short treatment time of 5 min. Lipid oxidation analyses performed on cheese and turkey samples indicated that the PHI treatment did not affect (P > 0.05) TBAR values. These studies suggest that LAE and GOX as antimicrobials and PHI treatment can be used as intervention strategies in an integrated process to ensure safe production of food. Further research is needed to evaluate applicability of SL and ACS in mozzarella cheese.
Keywords: Listeria monocytogenes; Ready-to-eat foods; Food contact surfaces; Food Science (0359)